Designing the Vocabulary Component for an EFL Cross-Cultural Communication Class - Tsubaki, Mayumi (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
A systematic course design is essential in order to achieve an optimal outcome for EFL learners. I will describe the course design of vocabulary components in a Cross-Cultural Communication class in a Japanese university. This course was designed according to the Content and Language Integrated Learning (CLIL) model, in which language learners learn the target language and content at the same time, rather than learning the target language, per se. In Cross-Cultural Communication classes of the CLIL model, learnersÃ¢â‚¬â„¢ English vocabulary develops as well as other language skills while they increase their knowledge of Cross-Cultural Communication. Some of the problems with this approach in Japan seem to lie in the studentsÃ¢â‚¬â„¢ insufficient English skills and their English learning backgrounds. I have attempted to design the course in order to solve these problems. I have mainly considered how to Ã¢â‚¬Å“fill the gapÃ¢â‚¬Â between what is needed to conduct the class and what the students lack, while focusing on vocabulary development of the university students in my class. I have employed two frameworks, the Curriculum Development Process (Nation & Macalister, 2010) and the four strands (Nation, 1996), and I have adapted them to suit my teaching situation. Curriculum Development Process consists of comprehensive factors necessary for curriculum development and has allowed me to analyze my present situation. On the other hand, the four strands approach is a well-balanced principle for vocabulary learning. It is supported by Second Language Acquisition (SLA) theories and has four components: meaning-focused input, meaning-focused output, language-focused learning, and fluency development. Although the Curriculum Development Process and the four strands approach mentioned here can be effectively applied to various foreign and second language learning situations, I found it crucial to analyze my teaching situation as much as possible, and to adapt these frameworks accordingly. This paper explains how a course can be designed with partial analysis of one's present teaching situation, in hope that this could offer some guidance to those who need to develop or improve their own course based on their best analysis under limited time.Keywords: Teaching and learning vocabulary, course design, English as a Foreign Language (EFL), the four strands,, content and Language Integrated Learning (CLIL)